Microchimerism in bone marrow-derived CD34+ cells of patients after liver transplantation - Nierhoff, Dirk; Horvath, Henrik Csaba; Mytilineos, Joannis; Golling, Markus T.; Bud, Octavian; Klar, Ernst; Opelz, Gerhard; Voso, Maria Teresa; Ho, Anthony Dick; Haas, Rainer; Hohaus, Stefan (Blood, 2000)
Lymphoid and dendritic cells of donor origin can be detected in the recipient several years after a solid organ transplantation. This phenomenon is termed microchimerism and could play a role in the induction of tolerance. The fate of other hematopoietic cells transferred by liver transplantation, in particular of stem and progenitor cells, is unknown. For this reason, we studied peripheral blood and bone marrow samples of 12 patients who had received a liver transplant from an HLA-DR mismatched donor. Eight patients were long-term survivors between 2.8 and 10.1 years after allografting. CD34+ cells from bone marrow were highly enriched with the use of a 2-step method, and a nested polymerase chain reaction was applied to detect donor cells on the basis of allelic differences of the HLA-DRB1 gene. Rigorous controls with DRB1 specificities equal to the donor and host were included. In 5 of 8 long-term liver recipients, donor-specific CD34+ cells could be detected in bone marrow. Microchimerism in the CD34+ cell fraction did not correlate to the chimeric status in peripheral blood. In conclusion, our results demonstrate a frequent microchimerism among bone marrow-derived CD34+ cells after liver transplantation. The functional role of this phenomenon still needs to be defined.
Elektronische Reproduktion der Druckausgabe
Das Pluszeichen im Titel ist hochgestellt
Gesehen am 21.12.2021